For the function g(x) = x2 + 5x - 2, determine g(-3x).
Follow Math Help Forum on Facebook and Google+
g(x) = x^2 + 5x - 2 g() = ()^2 + 5() - 2 so ... what would g(-3x) be?
Just sub -3x in for x and solve the equation.
Originally Posted by skeeter g(x) = x^2 + 5x - 2 g() = ()^2 + 5() - 2 so ... what would g(-3x) be? What are in placement of those happy faces? -3?
Originally Posted by william What are in placement of those happy faces? -3? Since the question asked g(-3x) (not g[-3]) you must sub in -3x not just -3 for the x's in the equation.
Originally Posted by skeeter g(x) = x^2 + 5x - 2 g() = ()^2 + 5() - 2 so ... what would g(-3x) be? g(-3x)= (-3x)^2+5(-3x)-2=9x^2-15x-2, correct?
g(-3x)= (-3x)^2 + 5(-3x) - 2 = 9x^2 - 15x - 2 there you go ... it wasn't that difficult, was it?
Originally Posted by skeeter there you go ... it wasn't that difficult, was it? quite simple
View Tag Cloud